Innovative nucleic acid detection of Clostridioides difficile utilizing the PAM-unconventional, one-step LAMP/CRISPR-Cas12b detection platforms - Zhang, Yizhuo; Lv, Luqin; Xu, Su; Chen, Yijian (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionClostridioides difficile (C. difficile), a human pathogen that causes diarrhea and colon lesions, has garnered widespread attention. Rapid and accurate detection of bacterial virulence factors is essential for the diagnosis of C. difficile infection (CDI). To date, numerous laboratory tests have been developed; however, none fully meet the combined requirements of speed, cost-effectiveness, portability, sensitivity, and specificity. Molecular diagnostic technologies based on CRISPR-Cas systems have provided a promising solution to this challenge. Nonetheless, the limited compatibility between pre-amplification and CRISPR cleavage, coupled with the inherent selectivity of CRISPR systems for protospacer adjacent motif (PAM) sequences near the target site, poses additional constraints on the broader adoption of this approach.MethodsHere, we developed PAM-unconventional, One-step LAMP/CRISPR-Cas12b (POLC) detection platforms for the toxin-encoding genes tcdA and tcdB of C. difficile.ResultsThe POLC platforms operated at 60 °C, enabling result interpretation either through fluorescence intensity measurements or direct visualization under UV light. The limits of detection (LoDs) ranged from 3 to 14 copies/μL using a fluorescence reader and from 6 to 18 copies/μL via direct observation. Compared to qPCR, which typically requires over an hour, the POLC platforms reduced the detection time to approximately 40 minutes. Each reaction cost approximately USD 6.5, offering a substantial cost saving compared to qPCR-based commercial kits (over USD 10 per test). In clinical validation with 55 fecal samples, the tcdA POLC assay achieved 86.4% sensitivity and 84.8% specificity, while the tcdB POLC assay demonstrated 96.6% sensitivity and 100% specificity, using qPCR as the reference standard.DiscussionOur research presents innovative CRISPR-based one-step nucleic acid detection platforms that eliminate canonical PAM sequence requirements. These platforms exhibit high sensitivity and specificity while achieving rapid detection under simple conditions, making them promising candidates for clinical diagnostics and point-of-care testing (POCT).